Модернізація корпусу плуга з обгрунтуванням його конструктивних параметрів - Кутковецька, Тетяна Олександрівна; Kutkovetska, Tetyana; Мелентьєв, Олег Борисович; Melentiev, Oleg (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті проведено дослідження щодо підвищення якості основного обробітку ґрунту шля-хом удосконалення робочих органів відвального плуга з обґрунтуванням його конструктивних параметрів. Наукову новизну становить установлення додаткових плоскорізальних робочих органів на кожному корпусі плуга з боку польового обрізу. При цьому практична цінність полягає в забезпеченні стійкості ходу орного агрегату, зниженні тягового опору та підвищенні якості глибокого розпушування ґрунту. Основні результа-ти дослідження показали, що запропонована установка додаткового робочого органу дозволить проводити пошаровий обробіток ґрунту й цим самим покращити якісні показники технологічної операції, що відпові-дають агротехнічним вимогам. Отримані дослідження показали, що запропоноване конструктивне технічне рішення забезпечить високу продуктивність роботи орного агрегату. /// EN: The article presents research on improving the quality of basic tillage by improving the working elements of a dump plow with a justification of its design parameters. It has been established that today many producers are returning to traditional technologies for growing crops and deep tillage with turning over soil plots, which occupies one of the main places. Therefore, it is important to increase the efficiency of dump plows for primary soil cultivation by improving their working elements. The scientific novelty in this study is the installation of additional flat-cutting working bodies on each plow body on the field edge side. The practical value lies in ensuring the stability of the plowing unit, reducing traction resistance and improving the quality of deep soil loosening. The main results of the study showed that a reduction in the draft resistance of the plowing unit and the energy intensity of the main tillage process with rotation of the soil clod can be obtained by improving the technological process of plowing, namely, by conducting layer-by-layer tillage. It can be noted that changing the shape of the cultivated soil layer should contribute to an increase in the angle of rotation of the soil clod, and maintaining the constructive width of the plow’s grip will prevent the violation of the geometric parameters of the working elements and thereby improve the quality of soil cultivation. It was determined that the proposed design with the use of additional working elements is operational with the following parameters: the length of the flat-cutting working element is up to 300 mm at a speed of up to 8 km/h. With these parameters, optimal agrotechnical and power performance indicators of the plowing unit are achieved, which fully meet the initial agrotechnical requirements. The obtained studies showed that the proposed constructive technical solution will ensure high productivity of the plowing unit.
Modernization of the plough body with substitution of its design parameters
Keywords: відвальна оранка; обробіток ґрунту; плоскорізальні робочі органи; тяговий опір; орний агрегат; леміш; польова дошка; розпушування ґрунту; технологічні операції; plow; dump plowing; soil cultivation; flat-cutting working elements; traction resistance; plowing unit; ploughshare; field board; soil loosening; technological operation